Nitrogen heterocyclic covalent organic frameworks for efficient H2O2 photosynthesis and in situ water treatment - Zhong Chen; Hao Weng; Chengcheng Chu; Ducheng Yao; Qiuju Li; Chen Zhang; Shun Mao (Nature Communications)
Abstract Nitrogen heterocyclic covalent organic frameworks offer great potential for H2O2 production due to their unique optical and electrical properties. Herein, we design four photocatalysts with varying nitrogen atom configurations to tune their electronic and energy-band structures. Among them, the covalent organic frameworks with pyrimidine achieves an efficient H2O2 production rate of 17014 μmol g−1 h−1 and a solar-to-chemical conversion efficiency of 1.84% in pure water without sacrificial agent or oxygen aeration. The theoretical calculation and experimental study confirm that it owns superior photoelectrochemical properties, oxygen reduction reaction activity, and the lowest reaction potential barrier, enabling dual channel H2O2 production via 2e− oxygen reduction reaction and 4e− water oxidation reaction. To explore the application potential of the photocatalytic system, a panel reactor (20 × 20 cm) under natural sunlight demonstrates continuous H2O2 generation for antibiotic degradation and long-lasting water disinfection. This work presents an advanced photocatalytic H2O2 synthesis system with high efficiency and environmental remediation potential.